Fruit Quality and Postharvest Performance of ‘Cripps Pink’ Apple in Relation to Withholding Irrigation - Wan Sembok, Wan Zaliha; Singh, Zora (International Society Horticultural Society, 2010)
We investigated the effects of withholding irrigation (WHI) at various stages of apple fruit development in improving fruit quality at harvest, particularly fruit colour without adversely affecting storage life and quality. WHI treatments were applied during stage II and III of fruit development commencing from 135, 145 and 155 days after full bloom (DAFB). Treatments were (i) T1, commercial irrigation as a control, (ii) T2, WHI from 135 to 153 DAFB, (iii) T3, WHI from 145 to 175 DAFB, and (iv) T4, WHI from 155 to 200 DAFB. WHI applied in T3 significantly reduced leaf water potential, 10 days after the commencement of WHI. WHI treatments did not significantly affect the cumulative fruit drop on 195 DAFB than T1. WHI treatment (T3) enhanced red skin colour, concentration of total anthocyanins, soluble solids concentration and firmness at harvest as compared to T1. Fruit from T3 stored at 0±0.1°C, 90±2% RH for 70 and 140 days retained higher firmness (>68N) and SSC (>15°Brix) as compared to T1.However, prolonged cold storage periods decreased titratable acidity of the fruit from irrespective of WHI treatments. WHI fruit from T3 stored for 140 days showed increased levels of ascorbic acid and total antioxidants in the pulp as compared to other treatments. In conclusion, WHI applied 145 to 175 DAFB (middle of stage II) improved fruit colour and other major fruit quality parameters at harvest without adversely affecting postharvest quality and also reduced water use.